Obesity and dysglycemia independently predict symptom burden but not satisfaction with care in polycystic ovary syndrome: a cross-sectional study - Bachmann, Annette; Estermann, Julia; Sourouni, Marina; Karn, Thomas; Bitterlich, Norman; Weidlinger, Susanna; Stute, Petra (Archives of gynecology and obstetrics, 2025)
Polycystic ovary syndrome (PCOS) is associated with a broad range of reproductive, metabolic, and psychosocial symptoms. This study aimed to evaluate whether body mass index (BMI) and dysglycemia independently predict symptom burden and to explore how these factors relate to patient-perceived care gaps, as reflected by satisfaction with counselling.
Gesehen am 13.02.2026